The Effect of Postpartum Exercise on Uterine Involution among Postpartum Mothers on the Third Day - Dewi S; Sumarmi; Kartini H, Anita; Ernawati; Nuryana, Riska; Hermadin; Ulfa, Marhaeni (Bantayang Omni Cendekia, 2025)
Background: Six weeks or forty-two days after childbirth is known as the postpartum phase (peueperium), during which the reproductive organs gradually recover similar to those that occurred before pregnancy. Objective: The description of postpartum gymnastics is known to decrease TFU on the third day. Methods: Quasy Experimental, Total population of 43 postpartum mothers, total sample of 30 mothers taken by accidental sampling technique. Results: Postpartum mothers who had participated in the gymnastics group and those who did not participated had the same results in terms of normal uterine involution, as many as 15 respondents (50.0%) each. Conclusion: Postpartum exercises performed regularly in accordance with the recommended method can strengthen the contraction of the uterine muscles. This causes ischemia by pressuring blood vessels, thereby reducing blood flow to the uterus and accelerating the shrinkage of uterine tissue.